The Influence of Work Motivation and Performance on the Job Satisfaction of Honorary Teachers at School X - Putri, Azzahra Namira; Wicaksono, Awang Setiawan (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
The purpose of this study is to determine the effect of work motivation and performance on job satisfaction of honorary teachers at SMK X. The background of this study is the low level of job satisfaction experienced by honorary teachers due to external factors such as salary and facilities, as well as internal factors such as work motivation. This research employs a quantitative approach using survey methods. The research population includes all honorary teachers at SMK X, totaling 34 individuals, who were sampled using total sampling. The data instrument utilizes a Likert scale to measure the variables of motivation, performance, and job satisfaction. Validity is tested with product moment correlation, while reliability is examined through Alpha Cronbach. The data is analyzed using regression tests with the help of SPSS software, including stages of normality, linearity, multicollinearity, and heteroskedasticity testing. The findings of the study show that both work motivation and performance have a significant effect.